Aspects of introducing digital technologies into the educational process (Journal of Science-Innovative Research in Uzbekistan, 2024)
This paper of this work is the importance of digital technologies in society is increasing. Technological improvements in education have made life easier for students. Today, instead of using pen and paper, students use different software and tools to create presentations and projects, unlike a heavy book, an e- book is easier to carry, they have what they need. an opportunity is being created for them to view information directly from the Internet through their gadgets or to study at two or more higher educational institutions at the same time. This article provides a brief overview of the need for digital technologies in education and discusses key applications and challenges in education.